Moth Assemblages (Lepidoptera: Heterocera) as a Potential Conservation Tool for Biodiversity Monitoring - Study in Western Himalayan Protected Areas - Dey, Pritha; Uniyal, V. P.; Sanyal, Abesh K. (Indian Forester, 2015)
Insects have long been ignored in the conservation approaches despite their fundamental roles in terrestrial ecosystems. Considering the lack in taxonomic expertise in the diverse insect groups, they are slowly making their way into the biodiversity monitoring studies. Moths belonging to the third largest insect order Lepidoptera are a hugely diverse and functionally important group, which can be a potential bio-indicator group in this present situation of environment degradation. Recent studies have brought this less studied group in focus for addressing conservation issues and a lot remains to be explored about this fascinating group of insects. In this paper we have shown some preliminary results of two studies done on moth assemblage in Western Himalayan Protected Areas. The studies aim to give an insight about the community structure and distribution patterns within the assemblages which can be a way forward for future bio-monitoring studies.